Writing exercises between coaching sessions to support Psychological - Fontes, A.; Dello Russo, S. (13th European Academy of Occupational Health Psychology Conference, 2018)
Coaching practices are increasing worldwide and, according to the meta-analysis by Jones and coauthors (2016), have significant positive effects on job attitudes, motivational outcomes, performance, and well-being. However, many differences exist across coaching practices with respect not only to who acts as coach (external, internal, self-coaching) but also features of the coaching delivery. In particular, the literature offers little guidance on specific techniques to use during or between sessions. Our aim in this study is to explore how writing exercises, assigned as homeworks between coaching sessions, can address and support individuals’ psychological capital, a critical resource for self-development. Psychological capital (PsyCap) is an individual’s positive psychological state characterized by self-efficacy, hope, optimism and resilience (Luthans et al., 2007) and is positively associated to wellbeing and positive work behaviors (Luthans & Youssef-Morgan, 2017). Therefore, PsyCap may be considered an outcome of coaching interventions in its own regards, and also an individual resource that makes coaching effective. We collected data from a sample of 27 employees working in a marketing company in Portugal, who were involved in a coaching program. Thus, this study is part of a larger project but here we focus on one specific technique used. Participants were asked to fill in three writing exercises (inspired to the reflective writing practice) in between one coaching session and another. They were required to reflect about: a) events that happened to them in relation to their developmental goals, since the last session, and their own behaviors, feelings and thoughts (1st exercise); b) positive events that happened to them in relation to their goals, since the last session, and their own behaviors, feelings and thoughts (2nd exercise); and finally c) overall progress towards their goals (3rd exercise). The texts were analyzed using NVIVO Software and coded following thematic analysis within the PsyCap framework. The results showed that the reflective writing exercises activated and likely strengthened the four PsyCap dimensions as internal resources for pursuing developmental goals. All three exercises targeted one or more of the PsyCap dimensions. The first exercise, compiled after the first coaching session during which development goals are set, therefore when individuals start acting toward their goals and are likely to have setback, was especially relevant for resilience (the ability to sustain and bounce back when facing obstacles). The second exercise, focusing on the positive episodes, was particularly relevant for self-efficacy (the confidence to take on and put effort to succeed), hope (the perseverance finding the paths toward goals) and optimism (the ability to make positive attributions). The third and final exercise, asking about progresses on one’s goals, targeted all four dimensions and the findings supported this. The small sample size suggests caution in reading these results, and yet they have further implications for coaching practices since the exercises could be fruitfully adopted in traditional but also online and self-coaching programs (Losch et al., 2016).